2016
DOI: 10.1596/1813-9450-7687
|View full text |Cite
|
Sign up to set email alerts
|

Bank Competition, Financial Dependence, and Economic Growth in the Gulf Cooperation Council

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In model 3, economic growth is negatively associated with non-performing loans at the 1% level, implying that bank instability (insolvency risk) harms economic growth. The results are consistent with earlier studies (Tabak et al, 2012;Caggiano & Calice, 2016;Gaffeo & Mazzocchi, 2014;Claessens & Laeven, 2005). Further, economic growth falls by 2.8% on average during the crisis.…”
Section: Bank Stability Competition and Economic Growth Using Systesupporting
confidence: 92%
See 1 more Smart Citation
“…In model 3, economic growth is negatively associated with non-performing loans at the 1% level, implying that bank instability (insolvency risk) harms economic growth. The results are consistent with earlier studies (Tabak et al, 2012;Caggiano & Calice, 2016;Gaffeo & Mazzocchi, 2014;Claessens & Laeven, 2005). Further, economic growth falls by 2.8% on average during the crisis.…”
Section: Bank Stability Competition and Economic Growth Using Systesupporting
confidence: 92%
“…According to Caggiano and Calice (2016), competition among banks affects economic growth in two ways: First, banking competition facilitates access to credit for small and new firms, which is important for economic growth. Second, companies dependent on external financing to run their operations are associated with slow patterns of economic growth; an increase in market power may hasten that economic growth (Hamada et al, 2018;Diallo & Koch, 2018;Mitchener & Wheelock, 2013).…”
Section: Related Literature and Research Focusmentioning
confidence: 99%
“…Under the banking context, increased market power could result in restricted loan supply and manipulated lending rates, thereby aggravating borrowers' financing constraints (Ryan et al, 2014). On the other side, a decrease in bank's market power enhances competition and increases the overall efficiency of a banking industry, therefore facilitating credit access (Meslier et al, 2020;Love and Peria, 2014), and ultimately leading to a stronger economic growth (Caggiano and Calice, 2016). While, the latter hypothesis (IBH, Petersen and Rajan, 1995) conjectures that, in the presence of information asymmetries and agency costs, fiercer competition may reduce the incentives of, or make it more costly for banks to invest in private information acquisition, and reduce the quality of screening and monitoring.…”
Section: : Introductionmentioning
confidence: 99%
“…Recent empirical studies, such as those conducted by Amidu and Wilson (2014), have found that competition in the financial sector encourages banks to innovate, reduce product prices, and improve product quality, thereby increasing consumer choice and growth. According to Caggiano and Calice (2016), competition in the banking sector can have a positive impact on economic growth in two ways: first, it makes it easier for small and new businesses to obtain credit; and second, it allows financially dependent businesses to grow more quickly. Their argument is that the advancement of these technologies has an impact on economic growth.…”
Section: Competition and Economic Growthmentioning
confidence: 99%